2022
DOI: 10.1093/heapro/daac120
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Community Readiness Model for childhood obesity prevention: a scoping review

Abstract: Summary The Community Readiness Model (CRM) provides an approach to determine community readiness (CR), which is the degree of a community’s preparedness to address a health issue. This scoping review aims to characterize internationally existing applications of the CRM for childhood obesity prevention. Therefore, a systematic literature research was conducted in PubMed, Cochrane Library, LIVIVO and Google Scholar. Of 285 identified records, 17 studies met the eligibility criteria and were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A scoping review conducted in 2022 found 17 studies worldwide that used the community readiness model for childhood obesity prevention. The average community readiness scores from studies without an intervention ranged from 1.6 to 6.08 [4]. These studies demonstrate the effective use of the community readiness model for assessing community preparedness to prevent childhood obesity.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…A scoping review conducted in 2022 found 17 studies worldwide that used the community readiness model for childhood obesity prevention. The average community readiness scores from studies without an intervention ranged from 1.6 to 6.08 [4]. These studies demonstrate the effective use of the community readiness model for assessing community preparedness to prevent childhood obesity.…”
Section: Introductionmentioning
confidence: 81%
“…These studies demonstrate the effective use of the community readiness model for assessing community preparedness to prevent childhood obesity. The review also identified five studies comparing the results of community readiness before and after an intervention [4]. Readiness scores increased after an intervention period of 2 to 5 years following "It's Your Move!"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Community Readiness Model (CRM), developed to guide the creation of community-level behavior change interventions, has been applied to a wide range of public health topics, including alcohol abuse, cardiovascular disease, and children's social-emotional development ( 19 – 22 ). A community's readiness varies by issue; for obesity, community readiness is often low or middling, in part because people may discount negative consquences of obesity that will accrue in the distant future ( 23 25 ). In this context, ILIs that target weight-related behaviors (e.g., diet or physical activity) may fail if they are not aligned with the community's highest priorities.…”
Section: Implementation Contextmentioning
confidence: 99%
“…Among these dimensions, the community's commitment in our study holds particular relevance to the concept of community readiness for prevention. Extensive research has highlighted the positive associations between community readiness and health outcomes ( Gansefort, Brand, Princk, & Zeeb, 2018 ; Kostadinov, Daniel, Stanley, Gancia, & Cargo, 2015 ; Schröder, Schnabel, Hassel, & Babitsch, 2022 ). Community readiness, as introduced by the Tri-Ethnic Center for Prevention Research ( Stith et al, 2006 ; Tri-Ethnic Center for Prevention Research, 2014 ), is closely related to community capacity as it reflects a community's preparedness and receptivity to address specific issues.…”
Section: Introductionmentioning
confidence: 99%